The Christmas turkey disaster - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 2015)
Hank is in real trouble this time. Loper and Sally May's relatives are coming for Christmas dinner, and Sally has been working to get the entire ranch in order...